THE ANALYSIS OF TRANSLATION PROCEDURES IN SUBTITLE OF â€œBOYCHOIRâ€ MOVIE - Syahrani, Nilda Iman; Tanduklangi, Amri; Muhsin, Muhammad Khusnun (Universitas Halu Oleo, 2019)
The purposes of this study are to anlyze the translation procedure and the way of the translator in translating the subtitle of Boychoir movie. The scope of this study is focusedÂ Â onÂ Â theÂ Â typeÂ Â ofÂ Â translationÂ Â proceduresÂ Â in translating the subtitle movie and also analyze the way of the translator in translating the subtitle on Newmarkâ€™s (1988:81) translation procedures which the procedures consist of 18 types. The methodology of this study was qualitative research. The researcher analyzed the data descriptively and presented the analysis result in the explanation form and supported by data presented in the form of table. In analyzing the data the procedures were as follows: juxtaposing both of English and Indonesian version, identifying, analyzing and classifying, and calculating the total numbers. The translation procedures found in the subtitle of the movie were literal translation, transference, naturalisation, culturalÂ Â Â Â Â equivalent, functional equivalent, synonymy, transpositions, modulation,Â Â Â Â reductionÂ Â Â Â andÂ Â Â Â expansion, couplets.Â Keywords: Translation, Translation procedure, Subtitle, Boychoir movie